Effects of plant growth regulators on growth and yield of pre-basic seed potato production under glasshouse condition (SAARC Journal of Agriculture, 2017)
A glasshouse experiment was carried out to study the effect of Plant Growth Regulators (PGRs) on the production of pre-basic seed (PBS) potatoes, cv. Janakdev at Khumaltar, (1360 masl) Lalitpur, Nepal during autumn and spring seasons of 2014 and 2015 respectively. Four - week old virus free in vitro plantlets grown in tissue culture laboratory were planted with 20 cm distance between rows and 10 cm between plantlets under glasshouse in completely randomized design. Three growth regulators, paclobutrazol (50 ppm), daminozide (100 ppm), chlormequat chloride (Cycocel) (200 ppm) and simple water as control were used for single foliar spray 6 weeks after transplanting with four replications. Analysis showed that there were significant differences on growth parameters; plant survival, plant uniformity, plant height and yield components; number of minitubers per plant and per square meter in both the seasons. Significantly maximum number of potato minitubers was recorded in growth retardants treated plants as compared to control. Experimental results showed that maximum number of minituber (22.9/plant and 668.2/m2) in autumn and (23.7/plant and 1185.0/m2) in spring season were gained from paclobutrazole spray, which were statistically differed from those of other growth regulators and control. Plants without PGR and treated with daminozide produced the least amount of minituber per unit area. Plant height decreased in all growth regulators over control due to their inhibiting effect on growth of the plants. paclobutrazol significantly reduced plant height but produced larger and heavier minitubers compared to other treatments. Hence, the best PGR for optimum enhancement of minituber number and size was paclobutrazol. The results suggested that paclobutrazol could be used in pre-basic seed potato production, leading to maximum minituber production which ultimately gave higher returns. The study concluded that spraying growth retarding chemicals at grand growth stage checked the excessive vegetative growth and increased the number and size of minituber.SAARC J. Agri., 15(1): 149-160 (2017)